2010
DOI: 10.1111/j.1745-4565.2009.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

OCCURRENCE AND CHARACTERIZATION OF STAPHYLOCOCCUS AUREUS ISOLATED FROM MEAT AND DAIRY PRODUCTS CONSUMED IN TURKEY

Abstract: A total of 413 samples of milk, dairy products, meat and meat products were analyzed for the presence of Staphylococcus aureus in a 2‐year survey (2004–2006). One hundred thirty‐eight samples were (33.4%) contaminated with S. aureus. A total of 138 S. aureus strains were isolated and identified. Enterotoksin profiles were determined by Staphylococcal Enterotoxin Test Reversed Passive Latex Agglutination. Their resistance to nine antibiotics were tested. The contamination rate of the meat product samples (48.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 26 publications
8
41
3
2
Order By: Relevance
“…1). Similar results were reported by Guven et al (2010). They isolated 138 S. aureus strains from 413 food samples collected in the Table 1 The presence of enterotoxin genes in S. aureus isolates.…”
Section: Prevalence Of Enterotoxin Producing S Aureus In Food Samplessupporting
confidence: 76%
See 1 more Smart Citation
“…1). Similar results were reported by Guven et al (2010). They isolated 138 S. aureus strains from 413 food samples collected in the Table 1 The presence of enterotoxin genes in S. aureus isolates.…”
Section: Prevalence Of Enterotoxin Producing S Aureus In Food Samplessupporting
confidence: 76%
“…Illness is caused by enterotoxin-producing S. aureus (Cha et al, 2006;Sudagidan and Aydin, 2009;Wieneke et al, 1993). Raw meat (Pereira et al, 2009), meat products, including fermented products such as sucuk (Guven et al, 2010), raw milk (Rall et al, 2008), dairy products (Normanno et al, 2007) and ready-to-eat foods, including bakery products (Oh et al, 2007) are among the foods reported to be associated with S. aureus enterotoxin-induced food poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of S. aureus in foods commonly indicates contamination that may be directly introduced into the food by workers who have skin lesions containing S. aureus, or by sneesing or coughing. Other contamination sources of S. aureus are soil, water, dust, and air (Gundogan et al 2005;Güven et al 2010). Table 1 shows the antibiotic resistance of enterococci strains isolated from chicken meat samples.…”
Section: Resultsmentioning
confidence: 99%
“…The raw meat group was the second source of contamination in this study. In contrast, Guven et al (2010) reported that the meat products contamination rate (48.7%) was significantly higher than milk and dairy products (23.2%) in Eskişehir and Kütahya region of Turkey. Although the rate of raw milk sample contamination was similar to their study, the controversy was originated from sample region.…”
Section: Resultsmentioning
confidence: 71%